Contested Terrain : Suburban Fiction and U.S. Regionalism, 1945-2020 - Wilhite, Keith (Book collections on Project MUSE., 2022)
"Drawing on a body of literature published between 1945 and 2016, Contested Terrain proposes a more expansive treatment of suburban fiction as a discourse that operates within national and transnational geographies. Wilhite argues that the suburbs and suburban narratives reflect the latest, perhaps final outpost in the tradition of U.S. regionalism. Although he may be accused of simply substituting one outmoded methodology for another, such a critique depends on misreading regionalism as either a sub-literary genre or, as Roberto Dainotto suggests, a pernicious political ideology that opposes modernity and suppresses difference in the naive pursuit of "grounded, rooted, natural, authentic values shared by a true community." In opposition to such withering appraisals, Contested Terrain demonstrates that, as both a literary discourse and a mode of geopolitical analysis, regionalism clarifies the fraught relationship between isolationism and imperialism that has shaped U.S. residential geography and, in turn, helps us rethink the role literary texts play in the postwar project of suburban nation building"--